Oil Palm Trunk of Lignocellulolytic Resources as Raw Material for Production of Fermentable Sugars via Enzymatic Hydrolysis Using Cellulose Thermostable - Marlida, Yetti; Arif, Syukri; Idris Tanjung, Aulia (Asian Journal of Chemistry, 2015)
This study aimed to explore the optimization of the concentration of oil palm trunks and thermostable cellulose enzyme preformance produce highest sugar (glucose total and reducing sugars) as well as the degree of polymerization. The design used in this study was a completely randomized design (CRD) factorial using 2 factors: factor A consists of four levels of cellulose enzyme that A1: 250 U/kg, A2: 500 U/kg, A3: 750 U/kg and A4: 1000 U/kg. Factor B is the concentration of oil palm trunk yitu B1: 20 % ; B2: 40 % and B3: 60 % were repeated 3 times. The results showed that there is a significantly effect (P < 0.05) in the levels of cellulose enzyme (factor A) with the concentration of oil palm trunks (factor B) and interactions of enzyme and oil palm trunk (factor AB) to reducing sugar, total sugars and degree of polymerization. This research can be concluded that the best total sugar produced was 19.68 mg/mL, the reducing sugars was 11.17 and degree of polymerization was 3.47.